2022
DOI: 10.1021/jacs.2c09050
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Asymmetric Catalysis Enables Direct and Enantioselective Decarboxylative Cyanation

Abstract: The development of efficient and sustainable methods for decarboxylative transformations is of great importance due to the ease of availability and nontoxicity of carboxylic acids. Despite tremendous efforts in this area, it remains challenging to develop enantioselective transformations direct from carboxylic acids. Herein we disclose a photoelectrocatalytic method for the direct and enantioselective decarboxylative cyanation. The photoelectrochemical reactions convert carboxylic acids to enantioenriched nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 85 publications
0
42
0
Order By: Relevance
“…In summary, we have developed a Cu-catalyzed enantioselective decarboxylative cyanation reaction in a synergistic fashion with the merger of photocatalysis and electrochemistry, which allows the direct decarboxylation coupling of simple carboxylic acids. 19 The current work demonstrates that this synergistic fashion could avoid the need for stoichiometric chemical oxidants or substrate prefunctionalization, in the meantime, enabling the reaction to operate under mild condition with high enantioselectivity and a reasonable range of functionalities. Further synthetic and mechanistic explorations of photoelectrocatalysis are currently underway.…”
Section: Discussionmentioning
confidence: 84%
“…In summary, we have developed a Cu-catalyzed enantioselective decarboxylative cyanation reaction in a synergistic fashion with the merger of photocatalysis and electrochemistry, which allows the direct decarboxylation coupling of simple carboxylic acids. 19 The current work demonstrates that this synergistic fashion could avoid the need for stoichiometric chemical oxidants or substrate prefunctionalization, in the meantime, enabling the reaction to operate under mild condition with high enantioselectivity and a reasonable range of functionalities. Further synthetic and mechanistic explorations of photoelectrocatalysis are currently underway.…”
Section: Discussionmentioning
confidence: 84%
“…In the metal Lewis acid catalysis strategies reported by Meggers [4][5] and Guo, [7][8][9] the metal catalyst not only induces chirality, but also promotes the electrochemical transformation of the substrate. The photoelectrocatalytic systems reported by Xu 28,30 and Liu 29 combine the advantages of photocatalysis and electrocatalysis to accurately realize the cyanation of benzylic C-H bonds. Clearly, electrochemical asymmetric catalysis has developed rapidly in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…29 At the same time, Xu and co-workers developed an efficient and sustainable method enables direct and enantioselective decarboxylative cyanation (Scheme 9c). 30 In this study, the Ce(OTf) 3 is converted into [CeCl 6 ] 3-, which is oxidized at the anode to [CeCl 6 ] 2-. The coordination of the carboxylate followed by photoinduced ligand-to-metal charge transfer (LMCT), regenerates Ce(III) and produces a benzylic radical after decarboxylation.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…33 In 2022, Song & Xu reported the first asymmetrical strategy of photoelectrochemical Ce catalysis (Figure 11a), achieving decarboxylative cyanation with high enantioselectivity. 34 From the substrate expansion, it can be speculated that the aromatic ring and alkyl group at βpositions of carboxyl, co-contributed to the chiral control. In addition, CV results showed that Ce III (Ep/2 ox =0.43 V vs SCE) was much easier to be oxidized than the carboxylic acid (Ep/2 ox = 2.0 V vs SCE), providing mild conditions for enantioselective synthesis.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%